ANALISIS PENURUNAN KADAR BESI (Fe) PADA AIR BERSIH DENGAN METODE MULTIPLE PLATFORM AERATOR DI PT. X (Jurnal Kesehatan Siliwangi, 2021)
The source of tap water in PT. Linico Indonesia is from groundwater. Iron (Fe) level in groundwater at PT. Linico Indonesia after checked is 6.11 mg/L and exceeds the quality standard. Then the groundwater treatment is carried out with the aeration process using the multiple platform aerator method. The purpose : to reduce iron (Fe) levels in groundwater and to determine the difference in platform height distances in the aeration process with the multiple platform aerator method with a platform height of 30 cm, 40 cm, and 50 cm. This type of research : experimental research with a pretest-posttest without control research design. The population : all of the groundwater used at PT. Linico Indonesia with sample size is 21,6 liters. The sampling technique is grab sampling. Collection data techniques : checking iron (Fe) level in laboratory, measurement temperature and pH of groundwater. Collection data instruments : spektrophotometer, thermometer for water, and pH meter. Research result : the average initial iron (Fe) content in groundwater is 6.11 mg/L. The average level of iron (Fe) in groundwater after the aeration process with a platform height distance of 30 cm is 3.29 mg/L with a percentage of 47.74%, 40 cm is 2.63 mg/L with a percentage of 54.79% and 50 cm which is 0.80 mg/L with a percentage of 86.45%. One-Way Anova test results : the p value 0.002 < 0.05 so that there is a difference in the distance of the platform height in the aeration process with the multiple platform aerator method on the decrease in iron (Fe) content. Recommendation : carry out further processing to filter the formed iron deposits.